1999
DOI: 10.1556/avet.47.1999.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Saccharomyces Cerevisiae 1026 Used Alone or With Vitamin-Mineral Premix on Biochemical Parameters of Blood and Milk in Dairy Cows

Abstract: When evaluating the effects of yeast culture (Saccharomyces cerevisiae $ ) supplied with or without a vitamin premix and mineral bioplexes on some intermediates and end-products involved in the synthesis of milk constituents in 30 earlylactation Black and White Lowland cows, no significant differences were found in the glucose level, mineral contents and enzyme activities of the blood serum. The effect of yeast culture on the availability of minerals for milk synthesis depended upon the dynamics of degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
(10 reference statements)
4
13
0
2
Order By: Relevance
“…The data could document a better absorption of these elements from organic forms. It is in agreement with experiments conducted by Iwańska et al (1999) and Strusińska (2003), who administered amino acid chelates to cows. In the 2 nd and 3 rd month after calving no differences in mineral contents in milk were noted.…”
Section: And Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The data could document a better absorption of these elements from organic forms. It is in agreement with experiments conducted by Iwańska et al (1999) and Strusińska (2003), who administered amino acid chelates to cows. In the 2 nd and 3 rd month after calving no differences in mineral contents in milk were noted.…”
Section: And Discussionsupporting
confidence: 92%
“…In experiments of Kinal et al (2005) on cows with average milk yield of 6 500 kg milk, who received Zn, Mn and Cu in organic forms, a significant increase in zinc and copper in blood serum was determined. The data confirm the results reported by Peterson et al (1987), Iwańska et al (1999) and Strusińska et al (2003), who indicated that the application of trace elements as chelates or yeast enriched with these microelements increased their bioavailability to rumen microorganisms and at the same time the possibility of better transfer of trace elements to the tissues, including blood. Other authors also pointed out this effect of the application of various forms of zinc and copper (Spears, 1996;Olson et al, 1999;Huert et al, 2002).…”
Section: And Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The same authors showed a significant increase in retention of total minerals, as well as potassium, copper, and zinc, when animals were fed a diet with live S. cerevisiae in comparison with the control ration. Moreover, Iwańska et al (14) showed that a supplement of live S. cerevisiae or mineral bioplexes increases the availability of minerals for ruminal microorganisms and increases their absorption to the blood of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Strusińska et al (13) showed that a live yeast supplement increased the zinc and iron concentrations in milk but decreased that of copper. Iwańska et al (14) did not observe any changes in the serum levels of calcium, phosphorus, magnesium, or iron, but an increase in the level of these minerals was found in milk.…”
Section: Introductionmentioning
confidence: 89%